Einstellungsgutscheine: Effektivität und Umsetzung - Alfred Boss; Alessio J. G. Brown; Christian Merkl; Dennis J. Snower (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
– This paper describes the practical implementation of hiring vouchers in Germany. According to our proposal, employers receive vouchers for hiring long-term unemployed, low-ability workers. Thereby labor costs are reduced for a limited period of time. The size of the vouchers increases with the duration of unemployment as well as with the qualification and it decreases with the subsequent employment duration. We specify a time profile for self-financing hiring vouchers for a broad range of unemployment durations and skills. We develop a simple formula to calculate the size of the voucher depending on the wage, the duration of unemployment and the subsequent employment duration.
Keywords: 330; Beschäftigungsgutschein - Effizienz; Lohnkostenzuschuss; Langzeitarbeitslose; Niedrigqualifizierte; Beschäftigungseffekte; Mitnahmeeffekte; Substitutionseffekte; Einkommenseffekte